Dynamic Linkages between Islamic Cryptocurrencies, Sukuk, and Islamic Stocks - Mahsa Pasca Genbi Muhammad; Sulistya Rusgianto (Universitas Airlangga, 2024)
This study aims to analyze the interdependence relationship between the Islamic cryptocurrency market, sukuk, and Islamic stocks through two different periods, namely bearish and bullish. This study uses daily market return data for December 31, 2019 - December 11, 2023 and the Markov Switching-Vector Autoregression (MSVAR) approach to analyze asymmetric behavior between markets. This study found several inter-market dependence relationships, including a bidirectional relationship with different effects between the Islamic cryptocurrency market and the sukuk market or the Islamic stock market and the sukuk market in bearish periods. There is also a two-way relationship with different effects between the Islamic cryptocurrency market and the sukuk market in bullish periods. Interestingly, there is a bidirectional relationship with the same negative effect between the Islamic cryptocurrency market and the Islamic stock market in bullish periods. Therefore, the combination of Islamic cryptocurrency market and Islamic stock market provides hedging benefits in bullish periods. Meanwhile, the combination of Islamic cryptocurrency market and sukuk market has potential as a diversification asset during bearish and bullish periods.